ARTIFICIAL SPEECH 2 - Redburn, Tamara L. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1983)
That computers can do the speaking for those who cannot speak must seem in the realm of magic, even in an age that gets bored with watching men on the moon. What is going on at Michigan State University under John Eulenberg must have immediate interest to anyone who is physically handicapped or who is working for people trapped in such conditions. The following two pieces offer, first, a glimpse of the human activities there as reported by John Moses, and second, a means of keeping in touch with what will yet be accomplished there and elsewhere, through the special publication edited by Tamara Redburn and devoted to these augmented and alternative forms of communication. There must be many among our readership who feel a strong need for this kind of connection, and this Journal is glad to give descriptive space to a publication that does such stimulating and urgent work in what is clearly a highly enterprising style. RÉSUMÉ Que les ordinateurs puissent parler à la place de ceux qui en sont incapables semble encore relever du domaine de la magie, même à une époque où l’on s’ennuie à regarder les hommes marcher sur la lune. John Eulenberg, de la Michigan State University, dirige un projet susceptible d’intéresser tous ceux qui souffrent d’un handicap physique ou qui travaillent avec les gens frappés de telles affections. Dans les deux exposés qui nous sont présentés, John Moses nous offre un aperçu des activités qui y sont réalisées, puis Tamara Redburn nous propose un moyen de garder le contact avec ce qui se fera là-bas et ailleurs, grâce à sa publication spéciale consacrée aux modes de communication perfectionnés et modifiés. Parmi nos lecteurs, nombreux doivent être ceux qui ressentent le besoin impérieux de ce genre de contact et ce journal est fier d’offrir l’espace nécessaire à une publication dont le travail urgent et stimulant touche un domaine de toute évidence extrêmement important.